KONTRIBUSI MEDIA SOSIAL ONLINE SEBAGAI SARANA PROMOSI PADA PRODUK MERV INDUSTRIES DI DESA KEPUH KABUPATEN SUKOHARJO - Inda Rezky Hermoyo; Abdullah Zailani; Zandra Dwanita Widodo (Universitas Bina Taruna Gorontalo, 2023)
The purpose of this study was to determine the influence of social media contributions WhatsApp, Facebook, and Instagram as a means of promotion of Merv Industries products. Then it aims to find out which social media has the most dominant influence as a promotional tool for Merv Industries products. This study used quantitative methods, collecting data through interviews and questionnaires. As for the population in this study are all consumers / product customers at Merv Industries. The sample was determined as many as 100 customers using the Cooper and Schindler methods. The COVID-19 pandemic has had a major impact on all aspects and sectors in people's lives, especially in the economic sector, resulting in many layoffs and a decrease in the number of buyers. To overcome the decline in the number of buyers, choosing to use marketing through social media is the main choice made by business actors. The results of the research based on the results of data processing show that partially or simultaneously there is a positive and significant influence on WhatsApp, Facebook and Instagram variables as a means of product promotion at Merv Industries. Then it is known that whatsapp has the most dominant influence as a means of product promotion at Merv Industries. The means of product promotion at the convection company Merv Industries are influenced by WhatsApp, Facebook and Instagram by 70.30%. While the rest, namely 29.70%, is influenced by other variables outside the variables examined in this study, including; service quality, company location and price discount.